Cure cycle analysis in thermoset polymers by thermal and mechanical analysis - Meza Mendoza, Guillermo; Chávez García, Dalia H.; López-Leyva, Josué Aarón; Ponce Camacho, Miguel Ángel (My University, 2018)
A thermoset polymer can be used for specific applications by creating a unique chemical composition that is designed for certain characteristic environments. To know the behavior of a thermoset polymer, it is necessary to thermally analyze its behavior during the curing process, as well as its mechanical behavior under certain loads that are applied in its field of application. In this study, the epoxy resin X was created at high temperatures, which there was no record of its thermal or mechanical behavior; the resin was analyzed to determine if it was possible to make a reduction in its curing cycle that was at temperature of 425° F with a time of 24 hours. As a result, through thermal analysis such as Differential Scanning Calorimetry (DSC), rheometry, Thermogravimetric Analysis (TGA) and Dynamic Mechanical Thermal Analysis (DMTA); as well as mechanical analysis, such as stress, hardness and planar cutting tests; it was possible to reduce the curing cycle of resin X, which is used in aerospace generators, from 24 hours at 425 ° F to 8 hours at 425 ° F. In the same way, this reduction of the cure cycle was verified by means of a qualification of a product that involved the reduction of the curing cycle of the epoxy resin obtaining very similar results to the original ones, verifying that the change of curing in the epoxy resin did not affected the functioning of the component. This methodology can be used and applied for the study of thermoset polymers that are used in several industries such as aerospace, automotive, among others.
MRS Advances
Keywords: Thermogravimetric analysis (TGA); Polymer